Distinct associations of self‐monitoring of blood glucose with glycemic control and hypoglycemia between groups of recently diagnosed and long‐term follow‐up type 2 diabetes: The Taiwan Diabetes Registry. Issue 9 (17th June 2021) - Wang, Jun‐Sing; Lo, Su‐Huey; Yeh, Yen‐Po; Hwu, Chii‐Min; Huang, Chien‐Ning; Hsieh, Chang‐Hsun; Sheu, Wayne Huey‐Herng
Abstract: Background: We investigated the uses and frequency of self‐monitoring of blood glucose (SMBG) with glycemic control and hypoglycemia in two groups of type 2 diabetes (T2D) (recently diagnosed and long‐term follow‐up) using real‐world data in Taiwan (the Taiwan Diabetes Registry). Methods: Patients with T2D recently diagnosed within 6 months (n = 3297, mean age 54.4 ± 13.9 years) and T2D patients with long‐term follow‐up (n = 1201, mean age 65.5 ± 12.1 years, mean diabetes duration 14.3 ± 7.8 years) from the Taiwan Diabetes Registry were analysed. All patients were interviewed by certified diabetes educators. Information about SMBG and hypoglycemia was recorded. Demography, personal history, and laboratory data were obtained from electronic medical records. Logistic regression analyses were used to examine the associations of SMBG with glycated haemoglobin (HbA1c) <7% and hypoglycemia. Results: Mean HbA1c values were 8.4 ± 2.5 and 7.6 ± 1.4%, respectively, in the recently diagnosed and long‐term follow‐up T2D groups. The self‐reported rates of hypoglycemic events within 3 months were 10.5% and 19.0%, respectively. SMBG was associated with higher odds of HbA1c <7% (OR 1.21, 95% CI 1.01‐1.44) in patients with recently diagnosed T2D, but with lower odds of HbA1c <7% in T2D patients with long‐term follow‐up (OR 0.60, 95% CI 0.44‐0.82). In both study populations, SMBG was independently associated with hypoglycemia (OR 3.90 [95% CI 2.99‐5.08] and OR 3.93 [95% CI 2.73‐5.66], respectively). The aforementioned findings were consistent across the strata of SMBG frequency. Conclusion: We reported different associations between SMBG and glycemic control in patients recently diagnosed with T2D and in T2D patients with long‐term follow‐up. SMBG was associated with higher detection of hypoglycemic episodes in both study populations.